Lake Mead Intake No 3 Tunnel – Design considerations and construction experience. Issue 1 (15th February 2018) - Anagnostou, Georg; Schuerch, Roberto; Perazzelli, Paolo
Abstract: This paper presents the pre‐construction evaluation of the ground for the Lake Mead Intake No 3 Tunnel and the experience gained from the project, which had the aim of maintaining water supplies for the Las Vegas greater metropolitan area. The construction of this tunnel using a dual‐mode slurry shield represents a major engineering achievement, which pushed back the boundaries of closed shield tunnelling: Overcoming an extended fault zone under high hydrostatic pressure in the metamorphic rocks and mucking‐out difficulties associated with high rates of water inflow in the sedimentary rocks necessitated closed‐mode operation over about 2 km at unprecedentedly high face pressures of up to 14 bar.